2002
DOI: 10.1177/152660280200900202
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Parodi Anti-Embolism System in Carotid Stenting: Italian Trial Results

Abstract: The PAES appears to be a safe and effective means of providing protection from embolic complications during carotid stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 23 publications
(34 reference statements)
1
49
0
1
Order By: Relevance
“…Patient selection, operator skill, and device design all remain important in optimizing outcomes in high-risk populations, including the very elderly. Previous, smaller investigations of flow reversal yielded results similar to those in the EMPiRE study [25,26,28,29]. In the largest of these, Parodi et al [28] employed flow reversal and Wallstents (Boston Scientific) to treat carotid artery stenosis in 200 patients.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Patient selection, operator skill, and device design all remain important in optimizing outcomes in high-risk populations, including the very elderly. Previous, smaller investigations of flow reversal yielded results similar to those in the EMPiRE study [25,26,28,29]. In the largest of these, Parodi et al [28] employed flow reversal and Wallstents (Boston Scientific) to treat carotid artery stenosis in 200 patients.…”
Section: Discussionmentioning
confidence: 72%
“…Subsequently, several studies found this method to be safe [25][26][27][28][29]. The Embolic Protection with Reverse Flow (EMPiRE) Clinical Study, which was conducted in the United States under an investigational device exemption from the US Food and Drug Administration (FDA), began in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature search resulted in 40 studies of CAS without cerebral protection and 14 studies of CAS with cerebral protection 17,30,[53][54][55][56][57][58][59][60][61][62][63][64] that met the inclusion criteria. Of these, several articles were excluded because they reported on patients already used in other publications from the same institutions: Theron et al 65 was excluded in favor of Guimaraens et al 58 ; several studies of the group of Roubin et al 36 -42 were excluded in favor of Roubin et al 32 ; Jordan et al 43 and Jordan et al 44 were excluded in favor of Jordan et al 22 ; Chakhtoura et al 45 62 One recent study 49 evaluating the efficacy of abciximab in patients undergoing CAS was also excluded.…”
Section: Resultsmentioning
confidence: 99%
“…1) By using a balloon and a filter device for distal protection and a double balloon catheter for proximal protection as EPDs, the procedure has been reported to be safe also for patients with vulnerable plaques, who have been considered a high-risk group for CAS, because a balloon is placed on the proximal side of the lesion, and debris is eliminated by flow reversal. 21) Ischemic tolerance has been reported as a problem in balloon protection, 22) but, by filter protection, the blood flow can be maintained, and the problem of ischemic tolerance can be avoided. However, the risk of passage of debris through the filter has been reported if the debris is smaller than the pore size of the filter or is liquid, or if a gap opens between the filter and vascular wall.…”
Section: Resultsmentioning
confidence: 99%